Di-μ-iodido-bis{[dicyclohexyl(phenyl)phosphine-κP](pyridine-κN)silver(I)} - Bernard Omondi; Reinout Meijboom (Acta Crystallographica Section E, 2009)
The title compound, [Ag2I2(C5H5N)2(C18H27P)2], contains centrosymmetric dinuclear species in which each Ag atom is surrounded by a phosphine ligand, a weakly coordinating pyridine ligand and two iodide anions in a distorted tetrahedral coordination. The two iodide anions bridge the Ag atoms, which are separated by a distance of 3.1008 (6) Å. The Ag—P distance is 2.4436 (8) Å, Ag—N is 2.386 (3)Å and the Ag—I distances are 2.8186 (4) and 2.9449 (5) Å.